Statistical analysis plan for Better Evidence for Selecting Transplant Fluids (BEST-Fluids): a randomised controlled trial of the effect of intravenous fluid therapy with balanced crystalloid versus saline on the incidence of delayed graft function in deceased donor kidney transplantation - Pascoe, Elaine M.; Chadban, Steven J.; Fahim, Magid A.; Hawley, Carmel M.; Johnson, David W.; Collins, Michael G. (Current controlled trials in cardiovascular medicine, 2022)
Delayed graft function, or the requirement for dialysis due to poor kidney function, is a frequent complication of deceased donor kidney transplantation that is associated with inferior outcomes. Intravenous fluids with a high chloride content, such as isotonic sodium chloride (0.9% saline), are widely used in transplantation but may increase the risk of poor kidney function. The primary objective of the BEST-Fluids trial is to compare the effect of a balanced low-chloride crystalloid, Plasma-Lyte 148 (Plasmalyte), versus 0.9% saline on the incidence of DGF in deceased donor kidney transplant recipients. This article describes the statistical analysis plan for the trial. BEST-Fluids is an investigator-initiated, pragmatic, registry-based, multi-centre, double-blind, randomised controlled trial. Eight hundred patients (adults and children) in Australia and New Zealand with end-stage kidney disease admitted for a deceased donor kidney transplant were randomised to intravenous fluid therapy with Plasmalyte or 0.9% saline in a 1:1 ratio using minimization. The primary outcome is delayed graft function (dialysis within seven days post-transplant), which will be modelled using a log-binomial generalised linear mixed model with fixed effects for treatment group, minimization variables, and ischaemic time and a random intercept for study centre. Secondary outcomes including early kidney transplant function (a ranked composite of dialysis duration and the rate of graft function recovery), treatment for hyperkalaemia, and graft survival and will be analysed using a similar modelling approach appropriate for the type of outcome. BEST-Fluids will determine whether Plasmalyte reduces the incidence of DGF and has a beneficial effect on early kidney transplant outcomes relative to 0.9% saline and will inform clinical guidelines on intravenous fluids for deceased donor kidney transplantation. The statistical analysis plan describes the analyses to be undertaken and specified before completion of follow-up and locking the trial databases. Australian New Zealand Clinical Trials Registry ACTRN12617000358347 . Prospectively registered on 8 March 2017 ClinicalTrials.gov identifier NCT03829488 . Registered on 4 February 2019.